Learning Japanese kanji characters using mobile games approach / Fadilah Ahmed Supian - Ahmed Supian, Fadilah (2012)
Japanese language has been introduced to our country as a third language nearly 50years ago. Because of it is a foreign language, certain problem arise among the learners especially on learning Japanese characters. This project is about developing a prototype of mobile application/game to solve problems related to Japanese kanji characters. Mobile phone is used as the medium of delivery and assist user in learning Japanese Kanji Characters. A test on the usability of the application showed that users are able to recognize kanji characters after using this application. One of the significance of this project is so that this game can be used as other alternative to study in a fun way.